Dividend Policy and its effects on firm value and share price volatility - Khattar, Nikhil (2012)
This paper aims to find the effect of Dividend policy if a firm on its market value and share price volatility. It is divided into 3 main parts. The first part reviews some of the literature that has been written till date about dividend policy. It describes the three schools of thought that have arisen as a result of varying views on the effect of dividend policy. The second part is regression analysis on 100 firms in the NYSE. These firms belong to five different industries: Consumer goods, Consumer services, Oil and gas, Industrials and Technologies. The third part consists of case studies on the dividend policy of three firms namely Microsoft, Florida Light and Power, Infosys and Hero MotoCorp. It gives a brief introduction of the companies and then analyses their recent dividend behaviour and how it has affected the value of the company.